Effects of Social Support, Functional Status, and Depression on the Quality of Life of Stroke Patients: A Meta-Analysis - Anwar Wahyudi; Didik Gunawan Tamtomo; RB Soemanto (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Stroke patients have physical, social, and psychological disorders. It inhibits their daily activities, thus affecting the quality of life. This study aimed to analyze the effect of social support, functional status, and depression on the quality of life of stroke patients.Subjects and Method: This study was a meta-analysis study. The data were obtained from Clinical Key, DOAJ, PubMed, Science Direct, Proquest, Scopus, and Google Scholar. The keywords were